2006
DOI: 10.1190/1.2358494
|View full text |Cite
|
Sign up to set email alerts
|

Gassmann's fluid substitution and shear modulus variability in carbonates at laboratory seismic and ultrasonic frequencies

Abstract: Carbonates have become important targets for rock property research in recent years because they represent many of the major oil and gas reservoirs in the world. Some are undergoing enhanced oil recovery. Most laboratory studies to understand fluid and pressure effects on reservoir rocks have been performed on sandstones, but applying relations developed for sandstones to carbonates is problematic, at best. We measured in the laboratory nine carbonate samples from the same reservoir at seismic ͑3 to 3000 Hz͒ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
136
2
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(153 citation statements)
references
References 31 publications
7
136
2
8
Order By: Relevance
“…Although S-wave velocity in soil is generally considered not to be much influenced by water saturation, experimental data and other studies (e.g. Iida 1938;Fratta et al 2005;Adam et al 2006;Lee and Collett 2006;Mondol et al 2007) indicate that shear modulus may be sensitive to saturation with fluids due to weakening of the soil matrix. Increased water content may also lead to increase of bulk density, which also contributes to velocity decrease.…”
Section: Results and Interpretationmentioning
confidence: 96%
“…Although S-wave velocity in soil is generally considered not to be much influenced by water saturation, experimental data and other studies (e.g. Iida 1938;Fratta et al 2005;Adam et al 2006;Lee and Collett 2006;Mondol et al 2007) indicate that shear modulus may be sensitive to saturation with fluids due to weakening of the soil matrix. Increased water content may also lead to increase of bulk density, which also contributes to velocity decrease.…”
Section: Results and Interpretationmentioning
confidence: 96%
“…The Gassmann theory assumes that shear moduli remain constant during fluid substitutions. Baechle et al (2005) as well as Adam et al (2006) showed that this is not the case in carbonate rocks, which are in many cases affected by shear weakening and shear strengthening, limiting the applicability of Gassmann's theory for the velocity prediction in carbonates. The travertines in this study, however, are crystalline with a matrix regularly consisting of micritic peloids, bound by sparites.…”
Section: Acoustic Velocity Measurementsmentioning
confidence: 99%
“…In the above example with synthetic unconsolidated sand (see Figure 1), ultrasonic velocities of dry and water-saturated samples could well be described by assuming the matrix stiffness is not affected by the water. For natural rocks, this assumption is often not valid; interaction with water often results in significant rock softening (Khazanehdari and Sothcott, 2003;Adam et al, 2006). The underlying mechanisms are not fully understood yet.…”
Section: Experimental Observationsmentioning
confidence: 99%